Regular Meals with Family and Its Association with Children’s BMI In Kota Kinabalu, Sabah - Alvin Oliver Payus; Constance Liew Sat Lin; Chandrika Murugaiah; Symeon Mandrinos; Rajesh Kumar Muniandy; Malehah Mohd Noh; Mya Sanda Khaing; Segaran Ramodran; Hamidah Hassan (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Nutrition is an issue of great academic and public importance. However, there is evidence that parents do not have family breakfast, lunch or dinner with their children. This study aims to assess the prevalence of having regular family breakfast, lunch, dinner among primary school children age 7 to 12 years in Kota Kinabalu and its association with children’s weight status. Methods: The study is based on 485 children (mean age: 11.5+/-0.7 years, 54% girls) randomly selected in five primary schools in Kota Kinabalu who participated in a cross-sectional school-based survey in 2019. Data on family meals were self-reported by the parents by answering a validated question¬naire. Children’s height and weight were measured to determine BMI status. Binary regression analyses assessed the associations of having regular family meals with children’s obesity status and to assess potential differences in having family meals according to gender and parental education. Results: The mean BMI male gender 24.3 ± 4.05 versus mean BMI female gender 17.9 ± 3.62 from 7 to 12 years old. The father mean BMI was 33.2 ± 8.24 versus 26.17 ± 9.63 mean BMI in mother from 32 to 52 years old. The prevalence of obesity within five (5) selected schools in Kota Kinabalu was only 13.2%. Regarding potential socio-demographic determinants, children of higher educated parents (STPM, DIPLOMA)[OR = 1.85 (95% CI 1.20–2.85)] were more likely to have breakfast together, while children of lower educated parents (SRP, SPM) [OR = 1.08 (95% CI 0.91–1.44)] were more likely to have dinner together. No significant associations of having family meals with gender observed. The prevalence of regular family meals was 94.6%, 74.17% and 93.8% for breakfast, lunch and dinner respectively. Conclusion: This study showed that having regular family breakfast, lunch and dinner was associated with children normal BMI between 18.50-24.99.